Applicability of molecular simulations for modelling the adsorption of the greenhouse gas CF4 on carbons. - Furmaniak, S.; Terzyk, A.; Gauden, P.; Kowalczyk, Piotr; Harris, P.; Koter, S. (Institute of Physics Publishing Ltd., 2013)
Tetrafluoromethane, CF4, is a powerful greenhouse gas, and the possibility of storing it in microporous carbon has been widely studied. In this paper we show, for the first time, that the results of molecular simulations can be very helpful in the study of CF4 adsorption. Moreover,experimental data fit to the results collected from simulations. We explain the meaning of the empirical parameters of the supercritical Dubinin–Astakhov model proposed by Ozawa and finally the meaning of the parameter k of the empirical relation proposed by Amankwah and Schwarz.